Taekwondo Training Improves Balance in Volunteers Over 40 - Pons Van Dijk, Gaby; Lenssen, Anton; Leffers, Pieter; Kingma, Herman; Lodder, Jan (Frontiers in Aging Neuroscience, 2013)
Abstract Balance deteriorates with age, and may eventually lead to falling accidents which may threaten independent living. As Taekwondo contains various highly dynamic movement patterns, taekwondo practice may sustain or improve balance. Therefore, in 24 middle-aged healthy volunteers (40-71 year) we investigated effects of age-adapted taekwondo training of one hour a week during one year on various balance parameters, such as: motor orientation ability (primary outcome measure), postural and static balance test, single leg stance, one leg hop test, and a questionnaire. Motor orientation ability significantly increased in favor of the antero-posterior direction with a difference of 0.62 degrees towards anterior compared to pre-training measurement, when participants corrected the tilted platform rather towards the posterior direction; female gender being an independent outcome predictor. On postural balance measurements sway path improved in all 19 participants, with a median of 9.3 mm/sec (range 0.71-45.86), and sway area in 15 participants with 4.2 mm²/sec (range 17.39-1.22). Static balance improved with an average of 5.34 seconds for the right leg, and with almost 4 seconds for the left. Median single leg stance duration increased in 17 participants with 5 seconds (range 1-16), and in 13 participants with 8 seconds (range 1-18). The average one leg hop test distance increased (not statistically significant) with 9.5 cm. The questionnaire reported a better ‘ability to maintain balance’ in sixteen. In conclusion, our data suggest that age-adapted Taekwondo training improves various aspects of balance control in healthy people over the age of forty.